Fresh-cut storage of fruit and fresh-cuts affects the behaviour of minimally processed Big Bang nectarines (Prunus persica L. Batsch) during shelf life. (March 2018) - Gallotta, Alessandra; Allegra, Alessio; Inglese, Paolo; Sortino, Giuseppe
Highlights: Big Bang fruit harvested at 50 N, could be stored at 1 ± 0.5 °C for no more than 10 d. Fresh-cut derived from fruit stored for 10 d had always the same fresh weight loss. The longer the fruit were stored before processing, the lower the L* of fresh-cut. Abstract: Nectarine can be minimally processed to successfully produce ready-to-eat fresh-cuts fruit. The aim of this work was to study the combined effect of the ripening stage of cold stored fruit before processing and the length of the storage period of fresh-cut slices after minimal processing, on the behaviour of minimally processed "Big Bang" nectarines during shelf life. 'Big Bang'nectarine slices obtained from fruit stored at 1 ± 0.5 °C (RH = 90%) for 1 d, 10 d and 15 d were stored for 0, 3, 5, 7, 12 d. at 5 °C. At the end of each storage period, visual quality, color (L*, a* and b*), phenols and carothenoids content, TSS, TA were measured together with in-package CO2 and O2 . Despite the more advanced ripening stage and the increase of polyphenol oxidase activity and ethylene production, nectarine fruit stored for 10 days were successfully processed to get fresh-cuts still marketable until 7 d after being cutting. Indeed, no difference occurred between fruit stored for 1 d before cutting and those stored for 10 d, in terms of firmness, weight loss and marketability of fresh-cut slices. The carotenoid content went descending dramatically in all samples of 'Big Bang' slices while in-package CO2 partial pressures were highest at 5, 7, 12 d of storage in fresh-cut to more from fruit stored for 1 d.